IMPLEMENTASI MEDIA PEMBELAJARAN DIGITAL WORDWOLL MELALUI PENDEKATAN ADDIE (STUDI KASUS PADA GURU SENI BUDAYA DI SMKS PARIWISATA BUBOHU) - Herman, Nurlia; Pulukadang, Mimy Astuty; Karlan, La Ode; Ohi, Rahmawati; Djafar, Nurlia (SINERGI : Jurnal Riset Ilmiah, 2025)
This research is motivated by field issues, particularly the continued use of one-way (lecture-based) teaching methods by educators, who predominantly rely on theoretical explanations from printed textbooks rather than engaging in practical activities. Furthermore, educators have not fully optimized the integration of digital media in the learning process, resulting in low student motivation and interest in learning dance. Meanwhile, based on the expected learning outcomes, students are required to create simple, creative dance performances according to their individual potential. This research aims to implement the digital learning media Wordwall, which can assist teachers in the teaching process while enhancing the understanding and learning motivation of Grade X students at SMKS Pariwisata Bubohu. Delivering material through lectures based on printed textbooks is considered ineffective in improving student’s understanding and experience in dance creation. The research employs a mixed methods approach. Data were collected through observation, interviews, documentation, and research instruments. The research subjects included individuals associated with the implementation of this research: the principal, arts and culture teacher, Grade X students of SMKS Pariwisata Bubohu, and lecturers from Universitas Negeri Gorontalo with expertise and interest in the fields of dance and language. This research employs the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research was carried out through several stages: needs analysis, media design of Wordwall, expert validation, classroom implementation, and evaluation. The results showed that the Wordwall learning media was highly valid for use, with validation scores of 92.5 from material experts, 90 from language experts, and 97.22 from educational media experts. The classroom implementation also showed an increase in understanding and learning interest, as seen in the teacher’s pretest-posttest results: the pretest yielded a score of -1.42 (indicating a decline), while the posttest yielded a score of 0.90 (high). Moreover, students’ responses to the Wordwall media were very positive, with final results categorized as “Very interesting/no revision needed.” This media has proven to enhance student’s comprehension and motivation, as well as support teachers in optimizing the learning process. The research also demonstrated that the ADDIE approach is an effective framework for developing learning media.